Analysis of Journalist Criminal Case Settlement from the Perspective of Progressive Legal Theory - Susanto, Joko; Pelupessy, Henry; Irawan, Irawan; Rian, Rinanda Asrian Ilmanta; Zen, Muhammad Alfin Aufillah (PT. Riset Press International, 2025)
This study aims to analyze the settlement of journalist criminal cases from a progressive legal perspective. The approach used is a literature study and analysis of related legal documents. This study identifies factors influencing the settlement of journalist criminal cases, including implementing progressive legal principles. From the results of the analysis, it was found that the application of progressive law can positively contribute to efforts to resolve journalist criminal cases more fairly and proportionally. The methodology that can be used includes data collection from various reliable sources, comprehensive analysis of relevant legal documents, and interviews with various related parties to obtain diverse perspectives. This study is expected to contribute to developing progressive legal theory and practice in resolving criminal cases for journalists in Indonesia.